Variability IN Ridge Gourd (Luffa Acutangula (Roxb.) L.) - Anitha CA (Department of Olericulture, College of Horticulture, 1998)
The present investigation on "Variability in ridge gourd (Luffa acutangula (Roxb.)L.)" was conducted at the College of Horticulture, Vellanikkara, Thrissur during 1997-98. Fifty seven accessions of ridge gourd collected from different parts of the country were grown in a randomised block design with two replications. The 57 accessions were genetically catalogued based on the descriptor of ridge gourd and LA 65 was observed as a hermaphrodite accession. Therefore it was not included in further statistical analysis. The extent of genetic variability for twenty characters viz. vine length, number of primary branches, internodal length, days to first female flower, nodes to first female flower, sex ratio, days to first harvest, fruitset, number of fruits per plant, yield per plant, average fruit weight, length of fruit, girth of fruit, thickness of flesh, number of ridges per fruit, seeds per fruit, 100 seed weight, duration of the crop, incidence of pests and diseases and fibre content were also studied. The fifty seven accessions were genetically catalogued based on the descriptor of ridge gourd. The genotypic and phenotypic coeffcients of variation, heritability, genetic advance and genetic gain were estimated. Significant difference were observed among the fifty six accessions for almost all the characters studied. Among the fifty six accessions, the earliest